Percutaneous minimally invasive thermal ablation for management of osseous metastases: recent advances. (1st October 2019) - Tomasian, Anderanik; Jennings, Jack W.
Abstract: Minimally invasive percutaneous thermal ablation of osseous metastases has proved safe and effective in management of selected patients with bone metastatic disease. These procedures have become a part of the treatment algorithm for certain subgroup of patients with osseous metastases to achieve pain palliation and/or local tumor control. This review details the armamentarium available and the most recent advances in minimally invasive, percutaneous image-guided thermal ablation for management of osseous metastases.